Some New Constructions of Authentication Codes with Arbitration and Multi-Receiver from Singular Symplectic Geometry - You Gao; Huafeng Yu (Journal of Applied Mathematics)
A new construction of authentication codes with arbitration and multireceiver from singular symplectic geometry over finite fields is given. The parameters are computed. Assuming that the encoding rules are chosen according to a uniform probability distribution, the probabilities of success for different types of deception are also computed.